Self-efficacy, perceptions of context, and burnout: a multilevel study on nurses - Consiglio, Chiara; Borgogni, Laura; Vecchione, Michele; Maslach, Christina (La Medicina del Lavoro, 2014)
Background: The role of personal and situational factors in burnout development in the hospital context is well known. The majority of studies used standardized and generic scales and focused exclusively on the individual level of analysis, underestimating the role of teamwork effects. Objectives: This study adopted a contextualized and multilevel approach in order to examine the different roles of individual and unit level nurse efficacy beliefs and hospital perceptions of context in predicting job burnout. Methods: Nurses (N=1020) belonging to 118 units completed two measures specifically tailored for the nursing environment: nurse self-efficacy, perceptions of context (teamwork, supervisor, management, and workload) together with MBI-GS exhaustion and cynicism scales. Multilevel confirmatory factor analysis was performed in order to verify the internal validity of nurse self-efficacy and hospital perceptions of context scales. A multilevel structural equation model was tested at individual and unit levels, using nurse self-efficacy, hospital perceptions of context and age as predictors of exhaustion and cynicism. Results: The good psychometric properties of the scales were confirmed. At individual level, nurse self-efficacy was the strongest predictor of both burnout dimensions. Exhaustion was also predicted by perception of workload and perception of management, while cynicism was also predicted by perceptions of teamwork, workload, and age. At unit level, perceptions of workload and teamwork emerged as predictors of unit exhaustion and cynicism, respectively. Conclusions: Based on our results, it is possible to plan distinct individual and/or unit-focused interventions in order to prevent hospital staff burnout.